Ovarian steroid cell tumors, not otherwise specified: three case reports and literature review - Sun, Yue; Tian, Lina; Meng, Chao; Liu, Guoyan (Frontiers in Oncology, 2024)
Objective To provide a reference for the diagnosis and treatment of ovarian steroid cell tumors, not otherwise specified (SCTs-NOS). Methods We retrospectively analyzed the clinicopathological data of three patients with SCTs-NOS admitted to the Tianjin Medical University General Hospital from 2012 to 2022 and reviewed literature reports related to this disease. Results A total of 3 cases in our center and 70 cases searched in literature reports were included. The age at diagnosis ranged from 3 to 93 years (median, 34 years). The common clinical manifestations were hirsutism, acne, deepened voice, clitoromegaly, amenorrhea, and excessive weight gain. Tumor sizes ranged from 1.2 to 45 cm, with an average diameter of 6.5cm. Most of SCTs-NOS were benign, but some of them exhibited malignant behavior. Surgery was the main treatment and close follow-up was required. The follow up time of 73 cases ranged from 3 to 132 months (median, 21.3 months). Disease recurrence or progression occurred in 14 cases (19.2%). Three of the 73 patients had a successful pregnancy. Conclusion SCTs-NOS usually occur in women of reproductive age, which are mainly manifested as androgen excess symptoms. Surgery is an appropriate treatment for SCTs-NOS and should be individualized. Final diagnosis depends on pathology. SCTs-NOS have malignant potential, and the treatments for patients with malignant tumors and disease recurrence or progression were cytoreductive surgery, adjuvant chemotherapy, and gonadotrophin-releasing hormone agonists (GnRHa) therapy.